2018
DOI: 10.1186/s13047-018-0281-2
|View full text |Cite
|
Sign up to set email alerts
|

Big issues for small feet: developmental, biomechanical and clinical narratives on children's footwear

Abstract: The effects of footwear on the development of children’s feet has been debated for many years and recent work from the developmental and biomechanical literature has challenged long-held views about footwear and the impact on foot development. This narrative review draws upon existing studies from developmental, biomechanical and clinical literature to explore the effects of footwear on the development of the foot. The emerging findings from this support the need for progress in [children’s] footwear science a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 76 publications
0
54
0
8
Order By: Relevance
“…The variability of shoe advice from health professionals may be challenging for parents [17, 18]. Previous studies have described optimum foot development occurring in a barefoot environment with the primary role of shoes being to protect the foot from injury [3].…”
Section: Discussionmentioning
confidence: 99%
“…The variability of shoe advice from health professionals may be challenging for parents [17, 18]. Previous studies have described optimum foot development occurring in a barefoot environment with the primary role of shoes being to protect the foot from injury [3].…”
Section: Discussionmentioning
confidence: 99%
“…Respondents reported difficulties with standard footwear accommodating orthotic devices (e.g., ankle–foot orthoses) leading to poorly fitting shoes. Appropriate footwear choices through the lifespan are important to protect the feet as well as provide support for the body during functional activities (Morrison et al, ), and these data add to an existing concern. Previous work in a sample of 50 children with Down syndrome identified that poorly fitting footwear was a source of pain and associated with increased levels of foot‐specific disability (Lim et al, ) and reduced physical activity levels (Shields et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The functional effects of foot problems are equally complex with gait changes (Galli et al, ) resulting in complex biomechanical movement characteristics which requires careful consideration during clinical consultation. Footwear has an important role in supporting the foot during weight‐bearing; yet, findings suggest that footwear problems are a frequent concern in children (Kennedy, McGinley, Paterson, Ryan, & Carroll, ; Lim et al, ; Morrison, Price, McClymont, & Nester, ; Prasher, Robinson, Krishnan, & Chung, ). Poor footwear fit can affect gait and balance (Kennedy et al, ; Wegener, Hunt, Vanwanseele, Burns, & Smith, ) and has been reported to be associated with increased levels of foot‐specific disability in children with Down syndrome (Lim et al, ) and reduced physical activity levels (Shields et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Humans have historically worn footwear for protection while walking [5]. However contemporary footwear choices are complex and influenced by a range of factors including financial, social and cultural pressures [6]. Interestingly, there is limited understanding about the effects of footwear choices on biomechanical factors that may influence foot development, and the emerging gait patterns of toddlers.…”
Section: Introductionmentioning
confidence: 99%